Apicomplexan Class XXVII Myosin - A Computational, Biophysical and Cell Biological Characterisation of PfMyoF in Plasmodium falciparum - Holmes, Alexander (Apollo - University of Cambridge Repository, 2024)
The Apicomplexan parasite P. falciparum, a lethal pathogen responsible for half a million deaths per year, relies upon myosin motor proteins for both transmission and virulence. Myosins are ATP-driven mechanoenzymes which either displace or translocate along actin filaments and typically function in a broad range of cellular activities such as membrane trafficking. Very little is known about the precise functions of the variety of myosins in P.falciparum or how they contribute to pathogenicity. The ultimate aim of this project is to biophysically and functionally characterise the essential P.falciparum myosin – PfMyoF. Bioinformatic analysis identifies novel features of both PfMyoF including two novel tail domains – a GTP binding and a WD40 domain. Bioinformatic, in vitro and cell-based assays have identified the regulatory light chains and suggest PfMyoF behaves as a plus end directed motor with a velocity similar to MYO5A. Antibodies generated against the PfMyoF tail domain have been used to examine endogenous localisation and perform pulldowns from parasites identifying putative binding partners suggesting a role for PfMyoF in membrane trafficking. Overall, this work advances our understanding of a key proteins within the complex cell biology of Plasmodium. Myosins are attractive targets for small molecule inhibitors and we anticipate that inhibition of PfMyoF could have great potential as a future antimalarial therapy.
Keywords: Malaria; Myosin; PfMyoF